2020
DOI: 10.1161/atvbaha.119.313414
|View full text |Cite
|
Sign up to set email alerts
|

Trimethylamine-N-Oxide Promotes Vascular Calcification Through Activation of NLRP3 (Nucleotide-Binding Domain, Leucine-Rich-Containing Family, Pyrin Domain-Containing-3) Inflammasome and NF-κB (Nuclear Factor κB) Signals

Abstract: Objectives: Vascular calcification is highly prevalent in patients with chronic kidney disease. Increased plasma trimethylamine N-oxide (TMAO), a gut microbiota-dependent product, concentrations are found in patients undergoing hemodialysis. However, a clear mechanistic link between TMAO and vascular calcification is not yet established. In this study, we investigate whether TMAO participates in the progression of vascular calcification using in vitro, ex vivo, and in vivo models. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
153
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 180 publications
(162 citation statements)
references
References 61 publications
7
153
0
2
Order By: Relevance
“…PERK is a receptor for TMAO, and its binding results in PERK activation and induction of the transcription factor FoxO1, a key factor in metabolic disorders [101]. Interestingly, TMAO may directly activate pro-inflammatory pathways as it up-regulates NLRP3 and nuclear factor (NF)-κB and thereby promotes vascular calcification [102]. Thus, TMAO reflects a crucial microbiota-derived biomarker of atherosclerosis and potentially of NAFLD-associated CVD.…”
Section: Trimethylamine N-oxide -Prototypic Microbiota-derived Metabomentioning
confidence: 99%
“…PERK is a receptor for TMAO, and its binding results in PERK activation and induction of the transcription factor FoxO1, a key factor in metabolic disorders [101]. Interestingly, TMAO may directly activate pro-inflammatory pathways as it up-regulates NLRP3 and nuclear factor (NF)-κB and thereby promotes vascular calcification [102]. Thus, TMAO reflects a crucial microbiota-derived biomarker of atherosclerosis and potentially of NAFLD-associated CVD.…”
Section: Trimethylamine N-oxide -Prototypic Microbiota-derived Metabomentioning
confidence: 99%
“…Phosphate-regulated intracellular signaling includes Wnt/β-catenin, protein kinase B (PKB or Akt), nuclear factor-kappa B (NF-κB), and serum-and glucocorticoid-inducible kinase 1 (SGK1) [57,[73][74][75][76]. The role of the inflammasome is also important [77,78]. In addition, oxidative stress, caused by an imbalance of antioxidants and reactive oxygen species (ROS), is related to osteoinductive signals and apoptosis, and may be regulated by the Gas6/Axl pathway, Akt, AMP-activated protein kinase (AMPK), etc., in which phosphate directly regulates apoptosis [77,79,80].…”
Section: Vascular Smooth Muscle Cell Phenotypic Differentiation In Himentioning
confidence: 99%
“…The role of the inflammasome is also important [77,78]. In addition, oxidative stress, caused by an imbalance of antioxidants and reactive oxygen species (ROS), is related to osteoinductive signals and apoptosis, and may be regulated by the Gas6/Axl pathway, Akt, AMP-activated protein kinase (AMPK), etc., in which phosphate directly regulates apoptosis [77,79,80].…”
Section: Vascular Smooth Muscle Cell Phenotypic Differentiation In Himentioning
confidence: 99%
“…[26][27][28] These translocated metabolites and toxins may then contribute to chronic inflammation and ultimately to cardiovascular disease. [29][30][31][32] Animal studies have shown that bile acids may have direct effects on cardiovascular calcification via farnesoid X receptor, a bile acid nuclear receptor. 33,34 In our study, bile acid synthesis was one of the top 3 pathways identified by the pathway enrichment analyses, but its pathway impact was low compared to that of arginine/proline metabolism and urea cycle (0.01 versus 0.21 and 0.23), and the association between the bile acid synthesis pathway and CAC status was not significant.…”
Section: Discussionmentioning
confidence: 99%